S-adenosylmethionine increases circulating very-low density lipoprotein clearance in nonalcoholic fatty liver disease - Martinez-Una, Maite (J Hepatol, 2014)
BACKGROUND: Very-low density-lipoproteins (VLDL) export lipids from liver to peripheral tissues and are the precursors of low-density-lipoproteins. Low levels of hepatic S-adenosylmethionine (SAMe) decrease triglyceride (TG) secretion in VLDL contributing to hepatosteatosis in methionine adenosyltransferase 1A knockout mice but nothing is known about the effect of SAMe over circulating VLDL metabolism. OBJECTIVE: We wanted to investigate whether excess SAMe could disrupt VLDL plasma metabolism and unravel the mechanisms involved. METHODS: Glycine N-methyltransferase (GNMT) knockout (KO), GNMT-PLIN2-KO and their respective wild types (WT) were used. A high fat diet (HFD) or a methionine deficient diet (MDD) was administrated to exacerbate or recover VLDL metabolism, respectively. Finally, 33 patients with nonalcoholic fatty-liver disease (NAFLD); 11 with hypertriglyceridemia and 22 with normal lipidemia were used in this study. RESULTS: We found that excess SAMe increases turnover of hepatic TG stores for secretion in VLDL in GNMT-KO mice, a model of NAFLD with high SAMe levels. The disrupted VLDL assembly resulted in the secretion of enlarged, phosphatidylethanolamine-poor, TG-and apoE-enriched VLDL-particles; special features that lead to increased VLDL clearance and decreased serum TG levels. Re-establishing normal SAMe levels restore VLDL secretion, features and metabolism. In NAFLD patients, serum TG levels are lower when hepatic GNMT-protein expression is decreased. CONCLUSION: Excess hepatic SAMe levels disrupt VLDL assembly and features and increase circulating VLDL clearance which will cause increased VLDL-lipid supply to tissues and might contribute to the extrahepatic complications of NAFLD. Electronic word count: 235